2020
DOI: 10.1111/adj.12786
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bleaching gel containing TiO2 and chitosan on tooth surface roughness, microhardness and colour

Abstract: Background: This study aimed to evaluate the effects of an experimental bleaching gel made with TiO 2 and chitosan, along with the Opalescence Boost PF and Philips Zoom bleaching agents, on tooth surface roughness, microhardness and colour. Materials and Methods: The experimental gel, containing 6% hydrogen peroxide (HP), was evaluated against the two existing treatments, which incorporate 40% and 25% HP. For colour evaluation, 36 human premolar teeth were divided into three groups (n = 12). For surface roughn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
(106 reference statements)
3
12
0
Order By: Relevance
“…Kwon et al [ 41 ] reported that the viscosity of the bleaching gel did not influence bleaching efficacy, but lower-viscosity gels increased hydrogen peroxide penetration. Although no significant increase in surface roughness values after bleaching with 40% HP was reported in the study by Kolsuz et al [ 42 ], in another study, a significant difference was observed in the surface roughness values, which is in line with the findings of the current study [ 43 ]. Here, the gels with 25% HP with nHA and 18% HP with nHA had lower viscosity than the other bleaching gels evaluated in the study.…”
Section: Discussionsupporting
confidence: 92%
“…Kwon et al [ 41 ] reported that the viscosity of the bleaching gel did not influence bleaching efficacy, but lower-viscosity gels increased hydrogen peroxide penetration. Although no significant increase in surface roughness values after bleaching with 40% HP was reported in the study by Kolsuz et al [ 42 ], in another study, a significant difference was observed in the surface roughness values, which is in line with the findings of the current study [ 43 ]. Here, the gels with 25% HP with nHA and 18% HP with nHA had lower viscosity than the other bleaching gels evaluated in the study.…”
Section: Discussionsupporting
confidence: 92%
“…That demonstrated low peroxide concentrations (6% HP) do not change surface roughness [29,45,48]. Although the roughness meter detects slight modi cations in the surface pattern of peaks and valleys, the reported values are minimal and will not cause consequences to the optical properties of the enamel nor will it increase the risk of bio lm formation -which could happen on surfaces with roughness values higher than 0.2µm [49].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, other studies concerning the demineralization and the microhardness of thinned enamel, before and after bleaching, have been controversial, and diversity of results has been obtained in the different works carried out. Some studies did not result in changes to the enamel surface after bleaching, nor was there change to the topography of enamel and dentin [33][34][35]. These studies concluded that despite using high concentrations of HP, the enamel was preserved.…”
Section: Discussionmentioning
confidence: 99%